A modification to the Goldstein radar interferogram filter - Baran, Ireneusz; Stewart, Michael; Lilly, Peter (IEEE Geoscience and Remote Sensing Society, 2003)
We present a modification to the adaptive Goldsteinradar interferogram filter which improves the quality ofinterferometry products. The proposed approach makes theGoldstein filter parameter alpha dependent on coherence, suchthat incoherent areas are filtered more than coherent areas. Thismodification minimizes loss of signal while still reducing the levelof noise.